2023
DOI: 10.3390/met13050832
|View full text |Cite
|
Sign up to set email alerts
|

Solid Salt Fluxes for Molten Aluminum Processing—A Review

Abstract: Aluminum recycling is a promising solution to environmental and economic issues. Secondary aluminum production will rise in the near future; however, the process is not without challenges. Some of the major concerns during remelting of aluminum are the metal losses due to the oxidation of the molten metal and the removal of impurities from the metal bath. The current study summarizes the latest progress in the use of solid salt fluxes for secondary aluminum production and the treatment of molten metal. The che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Fluxes are chemical elements or compounds that are added to metal melts to create a barrier restricting the interaction between oxygen in ambient air and active metals. Fluxing agents decrease metal oxidation, help remove impurities, and produce better quality materials [105]. Another function performed by fluxing compounds is lowering metal melting point and increase fluidity [106].…”
Section: Fluxing Agentsmentioning
confidence: 99%
“…Fluxes are chemical elements or compounds that are added to metal melts to create a barrier restricting the interaction between oxygen in ambient air and active metals. Fluxing agents decrease metal oxidation, help remove impurities, and produce better quality materials [105]. Another function performed by fluxing compounds is lowering metal melting point and increase fluidity [106].…”
Section: Fluxing Agentsmentioning
confidence: 99%
“…The fluxing process is one of the preeminent and extensively embraced methodologies for refining molten aluminium and eliminating oxide inclusions, including oxide films. Fluxes typically comprise solid substances designed to eliminate impurities and enhance the fluidity of the molten metal [10]. Shi et al, [11] also have found that the salt flux, comprising equimolar NaCl-KCl, can utilized to reclamation aluminium from waste aluminium and aluminium dross.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, a good TiB 2 inoculation practice provides sufficient time for the master alloy to dissolve and for TiB 2 particles to disperse in the melt [1]. On the other hand, caution needs to be exercised to avoid the decay of TiB 2 particles during different melt-handling steps, i.e., salt fluxing [4], melt transfer [5], melt holding, degassing [6,7], and filtration [8][9][10]. In order to determine the best location and timing for TiB 2 inoculation, it is imperative to know whether these melt-handling steps remove or lead to decay of the TiB 2 particles.…”
Section: Introductionmentioning
confidence: 99%